Three new records of Curcuma subgen. Ecomatae (Zingiberaceae: Zingibereae) for the flora of Laos - Souvannakhoummane, Keooudone; Souladeth, Phetlasy; Lanorsavanh, Soulovanh; Skornickova, Jana Leong (Thai Forest Bulletin (Botany), 2025)
Three species of Curcuma subgen. Ecomatae, Curcuma bicolor, C. nakhonphanomensis, and C. rubroaurantiaca, are newly recorded for the flora of Laos. Descriptions and colour plates, as well as notes on ecology and phenology, are provided for all three species. In addition, a key to species of Curcuma subgen. Ecomatae in Laos is also provided.